2021
DOI: 10.1103/physrevlett.127.018001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Isostatic Self-Dual Colloidal Crystals

Abstract: Self-dual structures whose dual counterparts are themselves possess unique hidden symmetry, beyond the description of classical spatial symmetry groups. Here we propose a strategy based on a nematic monolayer of attractive half-cylindrical colloids to self-assemble these exotic structures. This system can be seen as a 2D system of semidisks. By using Monte Carlo simulations, we discover two isostatic self-dual crystals, i.e., an unreported crystal with pmg space-group symmetry and the twisted kagome crystal. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 64 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Similar notions of dualities were suggested in systems ranging from self-assembled systems [10] to quantum rotors [11]. Rich consequences arise when a duality is combined with other constraints such as symmetries or conservation laws, ranging from degeneracies in the band structure [12][13][14] and topological states [15,16] to symmetries in the phonon response [17] and constraints on the stiffness tensor of an elastic medium [18].…”
Section: Introductionmentioning
confidence: 71%
“…Similar notions of dualities were suggested in systems ranging from self-assembled systems [10] to quantum rotors [11]. Rich consequences arise when a duality is combined with other constraints such as symmetries or conservation laws, ranging from degeneracies in the band structure [12][13][14] and topological states [15,16] to symmetries in the phonon response [17] and constraints on the stiffness tensor of an elastic medium [18].…”
Section: Introductionmentioning
confidence: 71%
“…Additionally, classical platforms possess unique properties beyond their condensed matter counterparts, benefiting interdisciplinary fields. Notably, long-range coupling, recently uncovered dualities, , fragile topology, topological quantum chemistry in photonics, and non-Abelian topological effects , can all pave the way for exciting topological phenomena for light propagation, sound, and mechanical vibrations in chemistry. Researchers are eager to harness this relatively new field in photonics, phononics, and interdisciplinary fields, for instance, by designing and fabricating disorder-immune components for high-speed information transfer and processing in on-chip designs integrated with optical or acousto-optic elements.…”
Section: Discussionmentioning
confidence: 99%
“…They varied the Janus balance (fraction of hydrophobic surface of the particle) and particle concentration and obtained onion phases, micellar, lamellar structures. Lei et al reported self-assembly of halfdiscs in 2D using depletion attraction between the curved sides [99]. They predicted a hexagonal lattice at high densities and gas phase at low densities.…”
Section: Patchy Particlesmentioning
confidence: 99%